2020
DOI: 10.1097/spv.0000000000000859
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age on Perioperative Complications After Minimally Invasive Sacrocolpopexy

Abstract: Objective Our aim was to compare perioperative complications between older (≥65 years), middle-age (55–64 years), and younger (<55 years) women after minimally invasive sacrocolpopexy (SCP). Methods This retrospective cohort study included women undergoing SCP from 2006 to 2016 at a single academic center. Our primary outcome was the rate of perioperative complications (intraoperative and postoperative within 6 weeks of surgery), between groups. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although a nonmodifiable risk factor, age is identified as a potential predictor for postoperative UTI in patients undergoing clean‐contaminated pelvic surgeries 15 . Many studies report higher incidence of UTIs after urogynecology surgery in older patients compared with their younger counterparts 24–27 with a few reporting a higher likelihood of postoperative UTI in younger patients 28,29 . In addition, the postbundle cohort had a significantly higher rate of vaginal surgical approach compared with the prebundle cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a nonmodifiable risk factor, age is identified as a potential predictor for postoperative UTI in patients undergoing clean‐contaminated pelvic surgeries 15 . Many studies report higher incidence of UTIs after urogynecology surgery in older patients compared with their younger counterparts 24–27 with a few reporting a higher likelihood of postoperative UTI in younger patients 28,29 . In addition, the postbundle cohort had a significantly higher rate of vaginal surgical approach compared with the prebundle cohort.…”
Section: Discussionmentioning
confidence: 99%
“…15 Many studies report higher incidence of UTIs after urogynecology surgery in older patients compared with their younger counterparts [24][25][26][27] with a few reporting a higher likelihood of postoperative UTI in younger patients. 28,29 In addition, the postbundle cohort had a significantly higher rate of vaginal surgical approach compared with the prebundle cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing complications in different age groups undergoing LSC, Edge et al 21 found that among their three groups (<55 years, 55–65 years, and >65 years), there were no differences in intraoperative complications. Women younger than 55 years (38%) were noted to have a higher rate of postoperative complications compared with women aged 55–65 years (38.0% vs 16.9%, P < 0.001) and also when compared with those older than 65 years (38.0% vs 20.1%, P = 0.001) 20 .…”
Section: Discussionmentioning
confidence: 99%